2006
DOI: 10.1212/01.wnl.0000234880.51322.16
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery in Parkinson disease

Abstract: After STN stimulation, patients experienced difficulties in their relations with themselves, their spouses, their families, and their socio-professional environment. The authors suggest a multidisciplinary psychosocial preparation and follow-up to help patients and their entourage cope with the sudden changes in their existence following successful neurosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
375
5
21

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(415 citation statements)
references
References 28 publications
14
375
5
21
Order By: Relevance
“…In two randomized trials comparing bilateral STN DBS with best medical therapy at 6-month follow-up, results correspond to an improvement of 17% and 25% in both DBS series, with almost no change in the medication groups (23,24). In other studies improvement of up to 68% has been reported in PDQ-39 at up to 24 months of follow up (13,21,11,20). Interestingly, an improvement in QoL in pallidal and subthalamic DBS after 2 years in a randomized trial was only moderate and reached 11.2% and 8.9% respectively (7).…”
Section: Disclosurementioning
confidence: 81%
“…In two randomized trials comparing bilateral STN DBS with best medical therapy at 6-month follow-up, results correspond to an improvement of 17% and 25% in both DBS series, with almost no change in the medication groups (23,24). In other studies improvement of up to 68% has been reported in PDQ-39 at up to 24 months of follow up (13,21,11,20). Interestingly, an improvement in QoL in pallidal and subthalamic DBS after 2 years in a randomized trial was only moderate and reached 11.2% and 8.9% respectively (7).…”
Section: Disclosurementioning
confidence: 81%
“…Overall, an adverse outcome may result from a combination of mental, societal and operational factors (94). Issues with cognition have also been reported, most notably deficiencies of language fluency (95).…”
Section: Long-term Side Effects Of Surgerymentioning
confidence: 99%
“…To our knowledge, only a small number of studies in the literature have specifically addressed the phenomenology of the self through a patient's subjective experience with DBS (de Haan et al 2015;de Haan et al 2013, Hariz et al 2011, Sch€ upbach et al 2006. A small number of case reports provide further insight into some of these postoperative changes to the self.…”
mentioning
confidence: 99%